Doxing Actions in Personal Data Protection - Salsabila, Arsha Chaizahra Putri; Wicaksono, Demas Brian; Seotijono, Irwan Kurniawan (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
With the rapid development of information technology, various types of cybercrimes have emerged, one of which is doxing. Doxing refers to the act of collecting and disseminating someone’s personal information without consent, with the intent to harm, embarrass, or intimidate the victim. This research aims to analyze the effectiveness of the PDP Law in addressing doxing in Indonesia. While the law Number 27 of 2022 on Personal Data Protection (PDP Law) can be applied to prosecute doxing perpetrators, Indonesia currently lacks explicit legislation specifically regulating this act. This study uses a normative juridical method with a statutory and case study approach. The results show that, compared to the previous Electronic Information and Transactions Law (ITE Law), the PDP Law provides stronger legal protection against doxing. Articles 65 and 67 of the PDP Law impose criminal sanctions for those who intentionally access, collect, or distribute personal data without legal authority. For example, the case of Febriansyah Puji Handoko in 2020 illustrates that if the case had occurred after the enactment of the PDP Law. Therefore, the PDP Law is considered relatively effective in providing legal protection for doxing victims. However, its implementation still faces challenges, such as the suboptimal function of the data protection authority and low levels of digital literacy in society.